El rol del trabajador social frente a la atención psicosocial, del Hospital Teófilo Dávila, de la ciudad de Machala, 2020 - Quezada Palacios, Kattia Jamileth; Suárez Pita, Génesis Noemí (Machala : Universidad Técnica de Machala, 2022)
The present work includes a series of results obtained based on the actions of the Social Worker and the multidisciplinary team that works with the users of the Teófilo Dávila Hospital in the city of Machala. On the other hand, delays have been identified with respect to the management, services, and resources, at the moment of influencing or intervening with the users who present mental health problems. On the other hand, a qualitative paradigm will be used in this project, this type of research includes concepts, opinions, or experiences, in addition, it can be used to obtain a deep vision of a problem or to generate new ideas for research. Qualitative research is the opposite of quantitative research, which involves the collection and analysis of numerical data for statistical analysis. At the methodological level, the psychosocial is related to the accompanying measures required by the user in emergency or problematic situations on a large scale, this implies that professionals from different areas form disciplines and immediately help the user or communities, this will ensure participatory and transformative actions. The psychosocial vulnerability presented by man derives from the characteristics of the socio-cognitive functioning of man and his relationship with his social environment, in addition, the relationship of both components allows the identification and evaluation of possible risks, within this component it is assumed the identification of individuals who are already affected by an occurring event. Based on both concepts, it will be possible to intervene with instruments or tools that help the individual in cases of psychosocial care, as well as to generate preventive programs that can support the risk situations of others. Therefore, we will proceed to perform a social diagnosis, it is intended to recognize the condition of any existing phenomenon or problem, at the same time this is accompanied by different phases that will help among them are. Diagnosis, which is responsible for studying the problem, its origin and performs a general data collection, formulation, objectives and goals are proposed to improve the problematic situation, implementation, the resources to be used are diagnosed and programmed, execution, the activities to be carried out to achieve the objectives and evaluation, the results obtained in this plan are corroborated, whether positive or negative. With the help of the observation technique, it became evident that currently the attention that the Social Worker provides to the users is excellent, and in order to receive attention in the Social Work area it is not necessary to take an appointment. Once this process is completed, the intervention proposal will be implemented in the city of Machala, province of El Oro, targeting users who are served in the area of psychosocial care adults, children, adolescents, pregnant women, etc. While it is true that mental health care is important for individuals, many of these individuals do not know how to relate or who to turn to for guidance or manage any resource in the hospital area. In general, it can be summarized which intervention plan has managed to strengthen the initiative of users and professionals of the Teófilo Dávila Hospital in the city of Machala, implying a positive and humanistic change for people who come to the psychosocial area.
El presente trabajo abarca una serie de resultados obtenidos basándonos en el accionar del Trabajador Social y el equipo multidisciplinario que incide con los usuarios del Hospital Teófilo Dávila de la ciudad de Machala. Por otro lado, se ha identificado retrasos con respecto a las gestiones, servicios y recursos, al momento de incidir o intervenir con los usuarios que presenta problemas de salud mental. Por otro lado, en este proyecto se va a utilizar un paradigma cualitativo, este tipo de investigación comprende conceptos, opiniones o experiencias; además, puede emplearse para obtener una visión profunda de un problema o generar nuevas ideas para la investigación. La investigación cualitativa es lo opuesto a la investigación cuantitativa, que implica la recogida y el análisis de datos numéricos para el análisis estadístico. A nivel metodológico, lo psicosocial está relacionado con las medidas de acompañamiento que amerita el usuario en situaciones de emergencia o problemáticas a grandes escalas, esto conlleva a que los profesionales de diferentes áreas formen disciplinas y ayuden de manera inmediata al usuario o comunidades, esto garantizara las acciones participativas y transformadoras. La vulnerabilidad psicosocial que presenta el hombre se deriva de las características del funcionamiento socio cognitivo del y su relación con su entorno social: además la relación de ambos componentes permite identificar y evaluar los posibles riesgos, dentro de este componente se asume la identificación de individuos que se encuentran ya afectados por un hecho ocurrente. A partir de ambos conceptos, se podrá intervenir con instrumentos o herramientas que ayuden al individuo en los casos de atención psicosocial, al igual que generar programas preventivos que puedan sustentar las situaciones de riesgo de los demás. Por ende, se procederá a realizar un diagnóstico social, está destinado a reconocer la afección de cualquier fenómeno o problema existente, a la vez esta acompaña de diferentes fases que ayudarán entre ellas están. Diagnóstico, que se encarga de estudiar la problemática, su origen y realiza una recolección de datos generales, formulación, se plantean objetivos y metas propuestas para mejorar la situación problemática, implementación, se diagnostica y se programan los recursos que se van a utilizar, ejecución, se realizan las actividades que se van a realizar para alcanzar los objetivos planteados y evaluación, se corrobora los resultados obtenidos en ese plan ya sean positivos o negativo. Con la ayuda de la técnica de observación se evidenció que actualmente la atención que la Trabajadora Social brinda a los usuarios es excelente, y para recibir una atención en el área de Trabajo Social no se debe sacar turno. Una vez terminado, todo esto proceso se procederá ejecutar la propuesta de intervención que está destinada a aplicarse en la ciudad de Machala, provincia El Oro, dirigiéndose a los usuarios que son atendidos en el área de atención psicosocial adultos, niños, adolescentes, mujeres embarazadas, etc. Si bien es cierto, la atención de salud mental eso es una importancia para los individuos; no obstante, muchos de esos individuos no saben cómo relacionarse ni a quién acudir por orientación o gestionar algún recurso en el área hospitalaria. A manera general, se puede sintetizar qué plan de intervención ha logrado fortalecer la iniciativa de los usuarios y profesionales del Hospital Teófilo Dávila de la ciudad de Machala, implicando un cambio positivo y humanístico para las personas que acuden al área psicosocial.
Keywords: HOSPITAL TEOFILO DAVILA; VULNERABILIDAD; TRABAJO SOCIAL; PSICOSOCIAL